ANALISIS KINERJA IT DENGAN MENGGUNAKAN IT BSC (STUDI KASUS PADA CV. SINAR REJEKI JAYA) - Reynold Andika; Hudi Prawoto (Jurnal Akuntansi Bisnis, 2012)
The purpose of this research is to know how information system being implemented in CV Sinar Rejeki Jaya. The model that being used to analyze the system is the IT BSC (IT Balanced Scorecard). The results of this research found that the performance of Distribution Application at CV Sinar Rejeki Jaya considered as good, based on four perspective of IT BSC. From Corporate Contribution Perspective, the Distribution Application proved that it improves work efficiency, in term of time and financial efficiency. From User orientation Perspective, the Distribution Application could gives ease to operational process, user satisfaction, information needs, and has better performance. In perspective of Operation excellence, the application has operational advantages, security advantage, and ease of use. And the last perspective, which is Future orientation perspective, The Distribution Application fasten and improves the whole business process. It cuts unnecessary cost. By having this advantages, the company could emphasize and concentrate on the business development.